Treatment of pure aortic regurgitation using surgical or transcatheter aortic valve replacement between 2018 and 2020 in Germany - Oettinger, Vera; Hilgendorf, Ingo; Wolf, Dennis; Stachon, Peter; Heidenreich, Adrian; Zehender, Manfred; Westermann, Dirk; Kaier, Klaus; von zur Mühlen, Constantin (Frontiers in Cardiovascular Medicine, 2023)
Background: In pure aortic regurgitation, transcatheter aortic valve replacement (TAVR) is not yet used on a regular base. Due to constant development of TAVR, it is necessary to analyze current data. Methods: By use of health records, we analyzed all isolated TAVR or surgical aortic valve replacements (SAVR) for pure aortic regurgitation between 2018 and 2020 in Germany. Results: 4,861 procedures – 4,025 SAVR and 836 TAVR – for aortic regurgitation were identified. Patients treated with TAVR were older, showed a higher logistic EuroSCORE, and had more pre-existing diseases. While results indicate a slightly higher unadjusted in-hospital mortality for transapical TAVR (6.00%) vs SAVR (5.71%), transfemoral TAVR showed better outcomes, with self-expanding compared to balloon-expandable transfemoral TAVR having significantly lower in-hospital mortality (2.41% vs 5.17%; p=0.039). After risk adjustment, balloon-expandable as well as self-expanding transfemoral TAVR were associated with a significantly lower mortality vs SAVR (balloon-expandable: risk adjusted OR=0.50 [95% CI 0.27; 0.94], p=0.031; self-expanding: OR=0.20 [0.10; 0.41], p<0.001). Furthermore, the observed in-hospital outcomes of stroke, major bleeding, delirium, and mechanical ventilation >48h were significantly in favor of TAVR. In addition, TAVR showed a significantly shorter length of hospital stay compared to SAVR (transapical: risk adjusted Coefficient=-4.75d [-7.05d; -2.46d], p<0.001; balloon-expandable: Coefficient=-6.88d [-9.06d; -4.69d], p<0.001; self-expanding: Coefficient=-7.22 [-8.95; -5.49], p<0.001). Conclusions: TAVR is a viable alternative to SAVR in the treatment of pure aortic regurgitation for selected patients, showing overall low in-hospital mortality and complication rates, especially with regard to self-expanding transfemoral TAVR.